EFFICACY AND SAFETY OF THERAPY WITH ATORVASTATIN IN HIGH DOSES - A. N. Meshkov (Рациональная фармакотерапия в кардиологии)
Large epidemiological trails shown that hypercholesterolemia is one of the main risk factor of ischemic heart disease (IHD). Correction of the hypercholesterolemia with GmGKoA reductase inhibitors (statins) essentially reduces IHD morbidity and mortality. The lower serum level of low density lipoprotein is - the lower risk of cardiovascular diseases and their complications are. Efficacy and safety of atorvastatin therapy in high doses is discussed in patients with IHD and dyslipidemia. Atorvastatin in high doses is more effective than standard therapy for prevention of cardiovascular complications. Atorvastatin is also effective in patients with recurrent cardiovascular events. Atorvastatin in high doses is safe and well tolerated. Serious side effects due to atorvastatin use (myopathy and rhabdomyolysis) are very rare. Generic atorvastatin 80 mg OD in ATLANTIC study was effective and safe. However efficacy and safety of other atorvastatin generics in dose of 80 mg OD is not well studied and it is necessary further studies.